Re‐reading of OraQuick HIV‐1/2 rapid antibody test results: quality assurance implications for HIV self‐testing programmes. (25th March 2019) - Watson, Victoria; Dacombe, Russell J; Williams, Christopher; Edwards, Thomas; Adams, Emily R; Johnson, Cheryl C; Mutseta, Miriam N; Corbett, Elizabeth L; Cowan, Frances M; Ayles, Helen; Hatzold, Karin; MacPherson, Peter; et al.
Abstract: Introduction: Scale‐up of HIV self‐testing (HIVST) will play a key role in meeting the United Nation's 90‐90‐90 targets. Delayed re‐reading of used HIVST devices has been used by early implementation studies to validate the performance of self‐test kits and to estimate HIV positivity among self‐testers. We investigated the stability of results on used devices under controlled conditions to assess its potential as a quality assurance approach for HIVST scale‐up. Methods: 444 OraQuick ® HIV‐1/2 rapid antibody tests were conducted using commercial plasma from two HIV‐positive donors and HIV‐negative plasma (high‐reactive n = 148, weak‐reactive n = 148 and non‐reactive n = 148) and incubated them for six months under four conditions (combinations of high and low temperatures and humidity). Devices were re‐read daily for one week, weekly for one subsequent month and then once a month by independent readers unaware of the previous results. We used multistage transition models to investigate rates of change in device results, and between storage conditions. Results and discussion: There was a high incidence of device instability. Forty‐three (29%) of 148 initially non‐reactive results became false weak‐reactive results. These changes were observed across all incubation conditions, the earliest on Day 4 (n = 9 kits). No initially HIV‐reactive results changed to a non‐reactive result. There were no significant associations between storage conditions and hazard of results transition. We observed substantial statistical agreement between independent re‐readers over time (agreement range: 0.74 to 0.96). Conclusions: Delayed re‐reading of used OraQuick ® HIV‐1/2 rapid antibody tests is not currently a valid methodological approach to quality assurance and monitoring as we observed a high incidence (29%) of true non‐reactive tests changing to false weak‐reactive and therefore its use may overestimate true HIV positivity.